THE INFLUENCE OF PRODUCT INVOLVEMENT AND PROMOTION MESSAGE ON MILLENNIALS MORTGAGE PURCHASE INTENTION IN INDONESIA - Andrea Theresia Manullang; Nurdin Sobari (SEAN Institute, 2023)
Investment is an activity by investing money or capital (valuable assets) for a certain period with the aim of obtaining profits or increasing the investment value in the future. In this era, all age generations have started to be concerned about making investments given the fluctuating economic conditions. Most novice investors choose investments with low risk, one example is property investment. Property investment is an investment in physical form which is considered to have low risk and is very profitable because the value continues to increase every year. One of the initial property investments is a house. Today's house is not only a residence, but also an investment asset for some people. However, currently the millennial is considered to still have difficulty buying their first home. Millennials are considered to still not see the importance of investing, especially in the property sector. With the Housing Loan (KPR) program, millennials can easily own housing as their initial investment in the property sector. For this reason, several factors are taken into consideration in selecting a mortgage, including trust in the mortgage lending bank, attractive promotional messages and program features offered.